SAM Sources and the DSeismic System: The Use in Marine Geological Mapping - CAR.G. and P.N.R.A. Projects - CORRADI, NICOLA; FERRARI, MARCO; IVALDI, ROBERTA; F. Giordano; A. Sbrana (MEDIMOND, 2009)
We describe the characteristics and uses of innovative Sparker source prototypes (SAM) and of a seismic signal acquisition/processing platform (DSeismic). The instruments were widely used in the CAR.G 2005-2008 (CARtografia Geologica) and in the P.N.R.A. (Programma Nazionale di Ricerche in Antartide) projects with the acquisition of more than 2000 km of very-high-resolution seismic lines in the Tyrrhenian Sea and in the Ross Sea, Antarctica (XVIIth and XXth cruises). The development of multi-electrode (SAM 96 and SAM 800 and SQUARE) electro-acoustical sources has enabled us to obtain very high vertical and horizontal resolution. The DSeismic acquisition platform, developed at the same time as the sources, has allowed us to elaborate the seismic-reflection data in real time.